A survey of CBT supervision in the UK: methods, satisfaction and training, as viewed by a selected sample of CBT supervision leaders. (14th October 2016) - Reiser, Robert P.; Milne, Derek L.
Abstract: Internationally, clinical supervision has been increasingly recognized as a core competency and an essential requirement for clinical training. Over the past 10 years, frameworks for supervision competencies have been developed and promulgated in several countries, notably the UK, USA and Australia. But what is the current status of the actual practice of CBT supervision in the UK? We conducted an internet survey with a purposive sample of n =110 accredited British Association for Behavioural and Cognitive Psychotherapy (BABCP) supervisors and trainers (a 44% response rate), selected for their assumed expertise. The results were consistent with past surveys of Townend et al., indicating that the most frequently reported supervision methods tended to reflect many of the recommendations in widely disseminated supervision competency frameworks and recognized best practice statements. Overall, these CBT supervision leaders reported using an impressively wide range of methods, including much more frequent use of role-play, therapy recordings, and direct observation than reported in the Townend et al . surveys or in observational studies. Although satisfied in their supervisory role, respondents indicated the need for improved CBT supervisor training resources, with significant interest in developing competence instruments and group supervision methods. In conclusion, at least for this small sample of CBT supervision leaders in the UK, practice reflects international progress, but training resources are sought to maintain momentum.